Argentina: Between Animal Rights Recognition and Animal Farming Intensification - Silvina Pezzetta (Revista Direito GV)
Abstract The intensification of animal farming is a growing trend worldwide that poses serious environmental and animal rights challenges. In Argentina, it gained public attention for the first time after the government agreed with China to install intensive pig farms in the country in 2020. Although the environmental danger raised the most important concerns among the public, the opposition also came from animal rights advocates. This paper will offer a theoretical analysis of intensive pig farming from animal ethics and animal welfare perspectives. The analysis will include how some of the most recent advances in Argentinean case law, recognizing legal personhood for some animals, could influence the path to animal farm intensification and its regulation. The work is divided into four sections. In the first, a brief discussion of the contributions of animal ethics will be presented. The second section will describe the main concepts involved in animal welfare science. In the third section, the article will describe the life and death of pigs on intensive farms. Finally, the last section will survey Argentinean animal rights case law and animal law, highlighting the contrast between the contradictory trends: animal legal personhood recognition versus animal farming intensification.